Comparative Analysis of Financial Performance Between Islamic and Conventional Banks: A Study of Efficiency, Profitability, and Risk Resilience - Ahmad Baidawi Ramadani; Sami Ayu Lestari (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
The global banking industry is currently dominated by a dual banking system, creating competition between conventional interest-based models and Islamic profit-and-loss sharing models. Although Islamic banks continue to grow by emphasizing ethical values and transparency, a research gap remains regarding long-term performance resilience, cost of capital structures, and operational efficiency (BOPO) compared to conventional banks, which are more established in terms of economies of scale and digital infrastructure. This study aims to map the performance divergence between these two banking systems to provide guidance for regulators and investors. This research employs a qualitative-descriptive design reinforced by a comparative quantitative approach. The units of analysis focus on Islamic Commercial Banks (BUS) and Conventional Commercial Banks (BUK) in Indonesia during the post-pandemic to recovery era (2020–2025). Secondary data were obtained through annual financial report documentation using a purposive sampling technique. The research instrument utilizes a modified CAMEL ratio framework, including Return on Assets (ROA), Non-Performing Loans/Financing (NPL/NPF), and the Capital Adequacy Ratio (CAR). Data analysis was conducted using the Independent Sample T-Test following Kolmogorov-Smirnov normality testing. The findings indicate that Conventional Banks consistently record higher profitability (ROA) due to economies of scale and the flexibility of interest-based instruments. While Conventional Banks are more operationally efficient (BOPO) due to established technological ecosystems, Islamic Banks maintain a higher Capital Adequacy Ratio (CAR) as a risk buffer. The acceleration of digitalization emerges as a key factor in narrowing the efficiency gap between these two banking systems